1966
DOI: 10.2118/1358-pa
|View full text |Cite
|
Sign up to set email alerts
|

Distribution in Fracture Permeability of a Granitic Rock Mass Following a Contained Nuclear Explosion

Abstract: In situ permeability of the rock outside the Hardhat chimney was determined by pressurization of long holes with air. Experimental data indicated a remarkable difference between fracture permeability of the rock near the chimney and that at a considerable distance. Although permeable fault zones were known to exist in the granite stock, the measurements of background permeability were quite low, on the order of tenths to several millidarcies. The observed difference is about two or three orders of magnitude ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

1973
1973
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…A significant fraction of the material appeared to be sand-sized. Boardman and Skrove (1966), which indicate the location and measured permeability or rocks in the vicinity of the Hard Hat test.…”
Section: Post-test Observationsmentioning
confidence: 99%
See 4 more Smart Citations
“…A significant fraction of the material appeared to be sand-sized. Boardman and Skrove (1966), which indicate the location and measured permeability or rocks in the vicinity of the Hard Hat test.…”
Section: Post-test Observationsmentioning
confidence: 99%
“…Cavity/chimney pressurization measurements suggested that wall rock permeabilities are on the order of 1,200 to 1,400 millidarcys (Boardman, 1965) (approximately 1 m/d). More direct measurements of rock permeability near the cavity/chimney were reported to be 200 to 2,000 millidarcys (0.2 to 1.7 m/d) and decaying exponentially to below 1 millidarcy with distance from the working point (Figure 2-9) (Boardman and Skrove, 1966). Interestingly, experimentally shocked granite samples could produce permeabilities as high as 0.5 millidarcy (4.2 x 10e-4 m/d) (compared to native rock permeabilities lower than 10 -6 millidarcy).…”
Section: Post-test Observationsmentioning
confidence: 99%
See 3 more Smart Citations